Sweet western sound [compact disc] - Tucker, Tanya; Carlile, Brandi (Fantasy, 2023)
Tanya Tucker's first album of new music since 2019's two-time Grammy Award-winning While I'm Livin', the reintroduction that revitalized her career and brought her music to a new generation of fans. While that album's stripped-down, singer-songwriter approach leaned toward the acoustic side, Sweet Western Sound's framework is more muscular, evoking, at times, the vintage West Coast country-rock productions of the '70s and '80s. Produced by Brandi Carlile and Shooter Jennings.